The geopolitics of green colonialism: Global justices and eco-social transitions - Lang, Miriam; Manahan, Mary Ann; Bringel, Breno (London Pluto press, Inc., 2024)
This book provides a platform for the voices that have been conspicuously absent in debates around energy and climate in the Global North. Drawing on case studies from across the Global South, the authors offer incisive critiques of green colonialism in its material, political and symbolic dimensions, discuss the multiple entanglements that forcefully connect the transitions of different world regions in a globalised economy, and explore alternative pathways toward a liveable and globally just future for all.
Keywords: Environmental justice; Green colonialism; Environmentalism political aspects